When Competition Eclipses Cooperation: An Event History Analysis of Joint Venture Failure - Park, Seung Ho; Russo, Michael V. (Management Science, 1996)
Why do so many joint ventures fail? Despite the fact that their success is the exception rather than the rule, the literature on why joint venture performance has been so poor remains fragmentary. We address this issue, adopting a transaction-cost economics perspective and modeling joint ventures as governance structures that blend the advantages and drawbacks of both markets and hierarchies. Using a data base on electronics industry ventures and event history analysis, we identify several predictors of joint venture failure and test for their influences. A key finding is that the presence of competition between joint venture partners outside of the agreement significantly impairs chances for the operation's chance of survival. We also find clear evidence that the failure rate of joint ventures is nonmonotonic, rising to a peak in the middle term and then declining. Finally, we compare and contrast predictors of terminations due to failure to those due to acquisition of the joint venture by one of its partners. Our overall conclusions highlight implications for strategic choice theory-building and the management of joint ventures.